Unstructured grid dynamical modeling of planetary atmospheres using planetMPAS: The influence of the rigid lid, computational efficiency, and examples of Martian and Jovian application. (May 2023) - Lian, Yuan; Richardson, Mark I.
Abstract: We present a new planetary global circulation model, planetMPAS, based on the state-of-the-art NCAR MPAS (Model for Prediction Across Scales) General Circulation Model. Taking advantage of the cross compatibility between WRF (Weather Research and Forecasting Model) and MPAS, planetMPAS includes most of the planetWRF physics parameterization schemes for terrestrial planets such as Mars and Titan. PlanetMPAS also includes a set of physics that represents radiative transfer, dry convection, moist convection and its associated microphysics for the Jovian atmosphere. We demonstrate that, despite the rigid-lid approximation, planetMPAS is suitable to simulate the climate systems in the Martian and Jovian atmospheres. Simulations using planetMPAS show that the new model can reproduce many aspects of the observed features on Mars and Jupiter, such as the seasonal CO2 cycle, polar argon enrichment, zonal mean temperature, and qualitative dust opacity on Mars, as well as the equatorial superrotation and banded zonal wind patterns on Jupiter. Highlights: A new planetary global circulation model is developed to simulate atmospheric circulations on Mars and Jupiter. PlanetMPAS is demonstrated to be suitable for simulating planetary atmospheres despite the rigid-lid approximation. PlanetMPAS improved physics parameterizations compared to MarsWRF, Mars MITgcm and other popular Jupiter GCMs. MarsMPAS is able to reproduce several observations on Mars including seasonal and variations of Argon enhancement. JupiterMPAS is able to produce equatorial superrotation and multiple banded zonal jets driven by moist convection.